Improving business performance through entrepreneurial orientation, product innovation, and co-creation value - Munawar, Muhammad Meki; Hurriyati, Ratih; Disman, Disman; Gaffar, Vanessa (International Journal of Innovative Research and Scientific Studies, 2023)
Business performance describes the ability of the manager of the company to perform. In micro, small, and medium companies, the owners usually act as the managers. Ideally, this performance has to be improved. Moreover, to accommodate this intention, this study investigates the related factors, like entrepreneurial orientation (EO), product innovation (PI), and co-creation value (CCV). Hence, this study aims to investigate two effects. The first is the impact of EO and CCV on PI. The second is the influence of CCV and PI on business performance. Therefore, a quantitative design is employed to examine the hypothesis by referring to this circumstance. As samples, this study uses a purposive sampling method to select 60 owners of the creative culinary industry in West Java. Additionally, this study uses a survey to collect the data, and the variance-based structural equation model to analyze the data. After processing the data, the hypotheses are tested and discussed, this research demonstrates the positive effect of EO and CCV on PI. Furthermore, a positive relationship is found between CCV and PI, and business performance. As a practical implication, entrepreneurial orientation, product innovation, and co-creation value are essential qualities for business owners to improve business performance.